Islamic sharia reform of Ahmadiyah sect in Indonesia - Moh Dahlan (HTS Teologiese Studies/Theological Studies, 2021)
Problems with the decline of Muslims have made the Ahmadiyah sect aware of the need to reform Islamic sharia. The purpose of the study was to reveal the problem of Islamic sharia reform in the Ahmadiyah sect. This study used scientific theory of Jurgen Habermas and content analysis techniques. This study indicated that the Ahmadiyah sect has difficulty in reforming Islamic sharia because it sought to develop Islamic religious sciences that can be embraced and used by majority of Muslims in Indonesia, but used the textual ijtihād paradigm. Even though, in the paradigm of social life (ḥifẓ al-nafs), the Ahmadiyah sect has succeeded in eliminating Muslims from setbacks and backwardness and building a life of peace and harmony in the social life diversity in Indonesia, but in the paradigm of religious life (ḥifẓ al-dīn), the Ahmadiyah sect was still a matter of contention in the Islamic world and Indonesia.